Penerapan Logika Matematika Dalam Ilmu Ekonomi Untuk Mendeskripsikan Permasalahan Korupsi - Susdarwono, Endro Tri (Universitas Dr. Soetomo, 2019)
Abstract The phenomenon of corruption can be analyzed using the principle of supply and demand. Corruption is synonymous with services traded between buyers and sellers, only that corruption is a product that harms anyone not involved in the transaction; in other words, corruption is built on negative externalities, which are losses that must be borne by others. The simplest argument for showing the economic costs of corruption is to associate corruption with wasted resources. This condition can be diagrammed through a